INVESTMENT SUPPORT OF HUMAN CAPITAL IN THE HR ENGINEERING SYSTEM IN THE CONDITIONS OF TRANSFORMATIONAL CHANGES - TELNOV, Anatolіі (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Management practice in the era of digital technology development shows a change in traditional approaches to personnel management. Today, the use of HR engineering systems allows you to adapt the internal environment of the enterprise and its structure to perform new tasks in the field of personnel management.The formation of human capital in wartime is an urgent problem that needs to be solved using sound scientific and methodological tools and from the standpoint of the systemic approach offered by HR engineering. Keywords: human capital, investments, investment support, system, HR engineering.In modern conditions, active investment support for the development and maintenance of human capital is necessary, both at the level of individual employers and from the allocation of priority areas of state policy to increase investments in the formation of favorable conditions for improving the quality of human resources, accessibility and quality of medical care, the development of education, the implementation of cultural policy.The purpose of the article is to summarize scientific approaches to investing in human capital under conditions of transformational change, to identify and justify their types by investment areas, and to determine possible results and expected effects from investment support for human capital.There are many problematic issues that require more in-depth and well-founded research, taking into account the impact of a number of negative processes caused by martial law and the general economic development of Ukraine.
Keywords: human capital; investments; investment support; system; social capital; HR engineering; transformational change; digital economy